Collective rationality : equilibrium in cooperative games - Weirich, Paul, 1946- (New York ; Oxford : Oxford University Press, 2009)
Groups of people perform acts that are subject to standards of rationality. The book's theory of collective rationality explains how to evaluate collective acts. The people engaged in a game of strategy collectively produce an outcome, and the theory reveals what makes some outcomes solutions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Game theory; Cooperation; Equilibrium (Economics)